Time course of natural heat acclimatization in well-trained cyclists during a 2-week training camp in the heat - Karlsen, A.; Nybo, L.; Nørgaard, S. J.; Jensen, M. V.; Bonne, T.; Racinais, S. (Scandinavian Journal of Medicine & Science in Sports, 2015)
The aim of this study was to determine the time course of physiological adaptations and their relationship with performance improvements during 2 weeks of heat acclimatization. Nine trained cyclists completed 2 weeks of training in naturally hot environment (34 ± 3 °C; 18 ± 5% relative humidity). On days 1, 6, and 13, they performed standardized heat response tests (HRT-1, 2, 3), and 43.4-km time trials in the heat (TTH-1, 2, 3) were completed on days 2, 7, and 14. Within the first 5-6 days, sweat sodium concentration decreased from 75 ± 22 mmol/L to 52 ± 24?mmol/L, sweat rate increased (+20 ± 15%), and resting hematocrit decreased (-5.6 ± 5.4%), with no further changes during the remaining period. In contrast, power output during TTHs gradually improved from TTH-1 to TTH-2 (+11 ± 8%), and from TTH-2 to TTH-3 (+5 ± 4%). Individual improvements in performance from TTH-1 to TTH-2 correlated with individual changes in hematocrit (assessed after the corresponding HRT; r = -0.79, P < 0.05), however, were not related to changes in performance from TTH-2 to TTH-3. In trained athletes, sudomotor and hematological adaptations occurred within 5-6 days of training, whereas the additional improvement in performance after the entire acclimatization period did not relate to changes in these parameters